Supporting university students with socially challenging behaviours through professional development for teaching staff - Veitch, Sarah; Strehlow, Karin; Boyd, James (2018)
In Australia and globally there is an increase in the numbers of university students presenting with diagnosed and undiagnosed equity and social inclusion issues related to disability and medical conditions, including mental health concerns and learning impairments. This paper discusses the collaboration between Learning Support, Equity and Social Inclusion, and Counselling to develop an introductory workshop for teaching staff. The workshop includes a specific focus on staff responses to what may be perceived as students’ socially challenging behaviours. This social dynamic sits within, and either reflects or collides with, the institution’s culture of inclusion. Our aim in this paper is to situate the importance of social relationships in the broader context of inclusive university education. We suggest that this is the grassroots level of institution and sector-wide cultural change that leads to staff engagement with universal learning design and curriculum reform. Our focus on the importance of social relationships between staff and students as a prerequisite of inclusive teaching and learning in higher education has implications for understanding the work that university teachers actually do, and highlights the complexity of university teaching as more than teaching discipline content. The paper argues for greater recognition of inclusive practice in teaching and learning in higher education.